Application of Traditional Chinese Medicine ointment combined with moxibustion in a patient with Liver-Qi stagnation and phlegm stagnation type hyperplasia of mammary glands and related nursing measures (中药膏摩联合艾灸治疗1例肝郁痰凝型乳腺增生患者的护理体会) - LI Suna (李苏娜); LIU Kexin (刘可欣); ZHENG Hongmei (郑红梅); TANG Ling (唐玲); CHEN Hong (陈宏) (中西医结合护理)
This paper summarized the nursing experience of a patient with Liver-Qi stagnation and phlegm stagnation type hyperplasia of mammary glands treated by Traditional Chinese Medicine (TCM) ointment rubbing combined with moxibustion. Nursing measures and efficacy observation of TCM ointment combined with moxibustion at Zusanli acupoint were performed. In addition to the targeted interventions by TCM syndrome differentiation, health education on dietary and emotion regulation was carried to achieve the effect of dredging milk collaterals, detumescence, relieving pain and improving gland hyperplasia. (本文总结了采用中药膏摩外敷联合艾灸足三里缓解乳腺增生症状的护理经验, 包括中药膏组方选择、膏摩操作方法、艾灸足三里的注意事项以及饮食指导、情绪疏导等常规护理方法, 全程基于中医辨证指导开展针对性措施, 从而达到疏通乳络、消肿散结、缓解疼痛、改善腺体增生状态的目的。)